Development of web-based digital libraries as learning resource facilities in elementary schools - Astiti, Ayu Dewi; Murti, Rahayu Condro; Hakiki, Muhammad (Universitas Padjadjaran, 2023)
The development of Information and Communication Technology (ICT) has greatly influenced the world of education. One of the benefits of using ICT in education is that it makes it easier to find learning resources that it’s used in the learning process is the school library through digital libraries. The schools should develop digital libraries with facilities adequately. This study aimed to develop prototypes of web-based digital library products suitable as learning resources at public elementary school. The type of research used was research and development (R&D) using the PPE (Planning, Production, and Evaluation) model, carried out at SDN Sindang III, Majalengka Regency. The subjects in this study were the school principal, ten teachers, and 43 students. The research instrument used observation, interview, and product validation sheets. Research data were analyzed qualitatively and quantitatively. The results of this research and development are web-based digital library products containing various textbooks adapted to the school curriculum, consist of 2013 curriculum books, Kurikulum Merdeka’s, numeracy literacy modules, children's story books, learning videos, and teacher-supporting books. The product validation by three experts and two practitioners using the DigiQUAL instrument, which consists of seven aspects, an average score of 4.4 is obtained, which is in the excellent category. Conclusion this study is innovation web-based digital library product can be a learning resource at SDN Sindang III, Majalengka Regency.